People’s Participation in Forest Management - Hegde, Harsha; Singh, Samom Khelen; Hegde, Nagaraj; Thakur, N. S.; Jha, S. K. (Indian Forester, 2011)
The effective and meaningful involvement of local communities has been attempted under the Joint Forest Management System in India by linking socia-economic incentives and forest development. Now it is realized that, true participation may lead to more effective conservation of forest resources. Based on the information from States as of March 2006, 106,482 committees are protecting 22.01 million ha of forests. People’s participation in forest management brought some of the positive changes like Change in attitude and relationship, improvement in the condition of the forest, reduction in encroachment rate, increase in the income, etc. Effort should be made to reduce the conflicts and need to plan forthe long future.